Carbon alloys novel concepts to develop carbon science and technology - Yasuda, Ei-ichi. (Amsterdam ; London : Elsevier, 2003)
In recent years the Japanese have funded a comprehensive study of carbon materials which incorporate other elements including boron, nitrogen and fluorine, hence the title of the project "Carbon Alloys". Coined in 1992, the phrase "Carbon Alloys" can be applied to those materials mainly composed of carbon materials in multi-component systems. The carbon atoms of each component have a physical and/or chemical interactive relationship with other atoms or compounds. The carbon atoms of the components may have different hybrid bonding orbitals to create quite different carbon components. Eiichi Yasuda and his team consider the definition of Carbon Alloys, present the results of the Carbon Alloys projects, describe typical Carbon Alloys and their uses, discuss recent techniques for their characterization, and finally, illustrate potential applications and future developments for Carbon Alloy science. The book contains over thirty chapters on these studies from as many researchers. The most modern of techniques, particularly in the area of spectroscopy, were used as diagnostic tools, and many of these are applicable to pure carbons also. Porosity in carbons received considerable attention.
Introduction. Space control in carbon alloys. Typical carbon alloys and their processing. The latest characterization techniques. Function developments and application potentials.
Includes bibliographical references and index.
Keywords: Carbon composites; Carbon; Alloys; Electronic books